Alimentary restriction in the productive revenve of Oreochromis niloticus - Arauco, Ricardo Romero; Costa, Vyvian Bezerra (Comunicata Scientiae, 2012)
The experiment was accomplished at the Laboratory of Mariculture of the Federal University of Maranhão. With the objective of evaluating the effect of the alimentary restriction in the productive acting of juvenile of tilapia of Nile (Oreochromis niloticus) cultivated in system of recirculation of water. It was used 300 juvenile of tilápia, distributed in 6 tanks of fiber-cement of 1000 L. The treatments were: (A) food supplied daily; (B) food supplied day yes and day no and (C) food supplied once every 2 days, being four repetitions for each treatment. They were appraised physiochemical parameters of the water and of productive acting. The results were submitted the variance analysis, and the averages were compared by the test Tukey, to 5% of probability. The quality of the water and the alimentary conversion were not influenced by the alimentary strategy. The productive acting presents differentiates significant (P <0,05) among the treatments, being the best for the fish fed daily without alimentary restriction, the worst for the fish fed once every 2 days. The alimentary restriction in fish reduces the growth performance.